Transverse Testicular Ectopia with Bilateral Pyocoele: Case Report and Brief Review of Literature - Kumar, Lokendra (J Surg Tech Case Rep, 2014)
Transverse testicular ectopia (TTE) is a rare anomaly in which both testis descend through a single inguinal canal and enter to same hemiscrotum. To the best of our knowledge, we are reporting a new variant of TTE with right inguinal hernia with bilateral pyocoele. In this case, both testes descend separately through corresponding inguinal canal and present in single right scrotum. There is no report of bilateral orchidectomy for this variant of TTE with bilateral pyocoele with calcified necrosed testes. We also describe its embryology and management in brief, and review the previously reported cases.